LEGAL PROTECTION OF WIFE AND CHILDREN IN SELF MARRIAGE - Nizla Rohaya; Suartini Supendi (Universitas Muhammadiyah Tangerang, 2020)
This study aims to contribute ideas in the form of knowledge to the public regarding the efforts that can be made by the parties to provide legal protection for wives and children in unregistered marriages, where unregistered marriages are generally known as valid marriages under sharia but are not recorded in administration. The state creates legal uncertainty for wives and children born in unregistered marriages. The research method used is the normative research method, where the author examines several positive laws governing marriage with various types. The contradiction in legal regulations that the authors found in the research results was then processed and analyzed. The authors found several solutions for wives and children born in unregistered marriages to obtain legal protection following the provisions of laws and regulations that are still valid but not known to the public. It is hoped that, from this research, there will be no more wives and children who are denied their rights because of the uncertainty of the status of Siri marriages.Keywords: Legal Protection, Wife, Children, Unregistered Marriage, Marriage Law